Community assembly and functional leaf traits mediate precipitation use efficiency of alpine grasslands along environmental gradients on the Tibetan Plateau - Shaowei Li (PeerJ, 2016)
The alpine grasslands on the Tibetan Plateau are sensitive and vulnerable to climate change. However, it is still unknown how precipitation use efficiency (PUE), the ratio of aboveground net primary productivity (ANPP) to precipitation, is related to community assembly of plant species, functional groups or traits for the Tibetan alpine grasslands along actual environmental gradients. We conducted a multi-site field survey at grazing-excluded pastures across meadow, steppe and desert-steppe to measure aboveground biomass (AGB) in August, 2010. We used species richness (SR), the Shannon diversity index, and cover-weighted functional group composition (FGC) of 1-xerophytes, 2-mesophytes, and 3-hygrophytes to describe community assembly at the species level; and chose community-level leaf area index (LAIc), specific leaf area (SLAc), and species-mixed foliar δ13C to quantify community assembly at the functional trait level. Our results showed that PUE decreased with increasing accumulated active temperatures (AccT) when daily temperature average is higher than 5 °C, but increased with increasing climatic moisture index (CMI), which was demined as the ratio of growing season precipitation (GSP) to AccT. We also found that PUE increased with increasing SR, the Shannon diversity index, FGC and LAIc, decreased with increasing foliar δ13C, and had no relation with SLAc at the regional scale. Neither soil total nitrogen (STN) nor organic carbon has no influence on PUE at the regional scale. The community assembly of the Shannon index, LAIc and SLAc together accounted for 46.3% of variance in PUE, whilst CMI accounted for 47.9% of variance in PUE at the regional scale. This implies that community structural properties and plant functional traits can mediate the sensitivity of alpine grassland productivity in response to climate change. Thus, a long-term observation on community structural and functional changes is recommended for better understanding the response of alpine ecosystems to regional climate change on the Tibetan Plateau.